2013
DOI: 10.1017/s0950268813002069
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacteriosis in returning travellers and potential secondary transmission of exotic strains

Abstract: Multilocus sequence types (STs) were determined for 232 and 737 Campylobacter jejuni/coli isolates from Dutch travellers and domestically acquired cases, respectively. Putative risk factors for travel-related campylobacteriosis, and for domestically acquired campylobacteriosis caused by exotic STs (putatively carried by returning travellers), were investigated. Travelling to Asia, Africa, Latin America and the Caribbean, and Southern Europe significantly increased the risk of acquiring campylobacteriosis compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…Furthermore, a study conducted in New Zealand that combined detailed epidemiological and genotyping data concluded that person-to-person transmission was responsible for 4% of campylobacteriosis cases in that country (74). Other studies, conducted in Australia and the Netherlands, provided similar figures for the contribution of person-to-person transmission to campylobacteriosis (300,379).…”
Section: Other Sourcesmentioning
confidence: 96%
“…Furthermore, a study conducted in New Zealand that combined detailed epidemiological and genotyping data concluded that person-to-person transmission was responsible for 4% of campylobacteriosis cases in that country (74). Other studies, conducted in Australia and the Netherlands, provided similar figures for the contribution of person-to-person transmission to campylobacteriosis (300,379).…”
Section: Other Sourcesmentioning
confidence: 96%
“…While genomic signatures of host association can transcend geographical structuring within C. jejuni and C. coli populations, there can be differences in the genotypes that are isolated from different countries (Asakura et al., ; Islam et al., ; Kivisto et al., ; Mohan et al., ; Prachantasena et al., ). This presents challenges, not only for attributing the source of infections among travellers returning from foreign locations (Mughini‐Gras et al., ), but also for understanding disease epidemiology in the context of a global food industry.…”
Section: Discussionmentioning
confidence: 99%
“…The variable outer membrane protein gene porA , which has been used as part of extended MLST schemes (Cody, Maiden, & Dingle, ; Dingle, McCarthy, Cody, Peto, & Maiden, ) was also among those genes with evidence of elevated recombination. This may explain why weak allopatric signals have been associated with sequence variation in the porA gene in addition to source attribution signals (Mughini‐Gras et al., ; Sheppard, Colles et al., ; Smid et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The variable outer membrane protein gene porA, which has been used as part of extended MLST schemes , Cody et al, 2009 was also among those genes with evidence of elevated recombination. This may explain why weak allopatric signals have been associated with sequence variation in the porA gene in addition to source attribution signals (Sheppard et al, 2010a, Smid et al, 2013, Mughini-Gras et al, 2014.…”
Section: (A) (B)mentioning
confidence: 99%